The feather and the stone - Shaw, Patricia, 1928- (London : Headline, 1992)
Historical romance set on an isolated cattle station in the Northern Territory.
Keywords: Frontier and pioneer life -- Australia -- Fiction; Women pioneers -- Australia -- Fiction; Young women -- Australia -- Fiction; Settlement and contacts - Settlers; Literature and stories - Non indigenous - Fiction; Race relations - Violent; Economic sectors - Agriculture and horticulture - Pastoral industry - Beef cattle; Race relations - Representation - Literature; Australia -- History -- 19th century -- Fiction; Northern Territory Top End (NT)